2020
DOI: 10.12965/jer.2040598.299
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physical fitness after an 8-week preseason training among elite football players aged 17–19 years

Abstract: There may be an optimal period of time to maximize the improvement of physical fitness during adolescence. The aim of this study was to examine the magnitude of changes in physical fitness after 8 weeks of preseason training according to chronological ages after the age at peak high velocity. Thirty male young football players from an elite football team (U-16, n= 10; U-17, n= 10; U-18, n= 10) participated in the study. The players completed an 8-week general preseason football training and participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Improvements in the majority of physical performance parameters (i.e., sprints, acceleration, total distance and max speed) following the six-week preparation training program are in line with previous findings of Lee and Joo [ 32 ] and Asadi et al [ 33 ], who reported improvements in fitness levels and/or sprint ability after eight and six weeks, respectively during preseason training in youth soccer players. Ehrmann et al [ 34 ] found an increase in distance/min (an indicator of workload intensity [ 35 ]) was associated with an increased risk of injury.…”
Section: Discussionsupporting
confidence: 90%
“…Improvements in the majority of physical performance parameters (i.e., sprints, acceleration, total distance and max speed) following the six-week preparation training program are in line with previous findings of Lee and Joo [ 32 ] and Asadi et al [ 33 ], who reported improvements in fitness levels and/or sprint ability after eight and six weeks, respectively during preseason training in youth soccer players. Ehrmann et al [ 34 ] found an increase in distance/min (an indicator of workload intensity [ 35 ]) was associated with an increased risk of injury.…”
Section: Discussionsupporting
confidence: 90%
“…4 Figure 3 of the diagnostic test results in this paper shows that the relative value of the maximum oxygen uptake of the athletes of the second national women's basketball team before the start of winter training is 42.56±2.92ml/ kg/min, which is far lower than the value of 53.73±4.55ml/kg/min of the National Women's basketball team reported by Chen Dechun and others, and also lower than the athletes of the National Women's handball team (52.4±4.1 ml/kg/min), indicating that the aerobic capacity of the athletes is not ideal. 5 The measurement of lactic acid resistance adopts the maximum intensity run of 5x300 m, 4 min in each interval, and blood is taken 3 min after the fifth 300 m run. The results show that the average value of blood lactic acid of the athletes of the second national women's basketball team is 11.19mmol/L, which is slightly lower than that of the National Women's basketball players (11.8±1.2mmol/L), indicating that the anaerobic ability of the athletes has reached a high level.…”
Section: Resultsmentioning
confidence: 99%
“…The distance covered in the shuttles was recorded for analysis. The YYIR1 is a valid and reliable predictor of high-intensity aerobic capacity and VO 2 max for various sports (Lee and Joo, 2020; Chaouachi et al. , 2012; Krustrup et al.…”
Section: Methodsmentioning
confidence: 99%
“…The distance covered in the shuttles was recorded for analysis. The YYIR1 is a valid and reliable predictor of high-intensity aerobic capacity and VO 2 max for various sports (Lee and Joo, 2020;Chaouachi et al, 2012;Krustrup et al, 2003). After the test, the estimated VO 2 max was calculated using the following formula by Bangsbo et al (2008).…”
Section: Exercise Performance Measurementsmentioning
confidence: 99%